2012
DOI: 10.1021/ci3004489
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Affinity Fingerprints for Target Fishing: A New Application of Drug Profile Matching

Abstract: ABSTRACT:We recently introduced drug profile matching 12 (DPM), a novel virtual affinity fingerprinting bioactivity pre-13 diction method. DPM is based on the docking profiles of ca. 30 Finding compounds for a given target is a common computa-31 tional task in a conventional medicinal chemistry program. However, 32 by means of increasingly available bioactivity data, this 33 approach can be reversed to finding targets for compounds. 34 In silico target fishing 1 is an emerging field that aims at pre-35 dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…The starting hypothesis behind DPM is that similar affinity fingerprints refer to similar bioactivity properties (ie, targets and medical effects). We found that there is a strong relationship between the 177 medical effects studied and 77 target categories with the virtual affinity fingerprints of the drugs 3. Receiver operating characteristic analysis and cross-validations proved that the method is robust, and the affinity fingerprints provide enough information to recreate the effect profiles of drugs.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The starting hypothesis behind DPM is that similar affinity fingerprints refer to similar bioactivity properties (ie, targets and medical effects). We found that there is a strong relationship between the 177 medical effects studied and 77 target categories with the virtual affinity fingerprints of the drugs 3. Receiver operating characteristic analysis and cross-validations proved that the method is robust, and the affinity fingerprints provide enough information to recreate the effect profiles of drugs.…”
Section: Introductionmentioning
confidence: 87%
“…This method uses virtual affinity fingerprints of small molecule compounds to predict their medical effects and targets 2,3. In DPM, the affinity fingerprint is called IP, which consists of a set of docking scores of a compound against the binding sites of a predefined nontarget protein set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative structure−activity relationship (QSAR) approach is a useful tool for optimizing leads and predicting target/off‐target activities and toxicity. QSAR‐based affinity predictions are useful for the general drug development process, including the repositioning (repurposing) of already approved drugs, poly‐pharmacology, and the prediction of drug−drug interactions . The recent accumulation of protein−compound affinity data in public repositories, such as the PubChem and ChEMBL projects, has enabled us to carry out proteome‐wide target/off‐target predictions ,.…”
Section: Introductionmentioning
confidence: 99%
“…QSAR-based affinity predictions are useful for the general drug development process, including the repositioning (repurposing) of already approved drugs, poly-pharmacology, and the prediction of drugÀdrug interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The recent accumulation of proteinÀcompound affinity data in public repositories, such as the PubChem and ChEMBL projects, has enabled us to carry out proteome-wide target/off-target predictions. [16,17] These predictions are based on QSAR models for multiple proteins, just as in conventional computer-aided drug design and virtual screening.…”
Section: Introductionmentioning
confidence: 99%